Spectrum splitting using multi-layer dielectric meta-surfaces for efficient solar energy harvesting - Yao, Yuhan; Liu, He; Wu, Wei (Applied physics. A, Materials science & processing, 2014)
We designed a high-efficiency dispersive mirror based on multi-layer dielectric meta-surfaces. By replacing the secondary mirror of a dome solar concentrator with this dispersive mirror, the solar concentrator can be converted into a spectrum-splitting photovoltaic system with higher energy harvesting efficiency and potentially lower cost. The meta-surfaces are consisted of high-index contrast gratings (HCG). The structures and parameters of the dispersive mirror (i.e. stacked HCG) are optimized based on finite-difference time-domain and rigorous coupled-wave analysis method. Our numerical study shows that the dispersive mirror can direct light with different wavelengths into different angles in the entire solar spectrum, maintaining very low energy loss. Our approach will not only improve the energy harvesting efficiency, but also lower the cost by using single junction cells instead of multi-layer tandem solar cells. Moreover, this approach has the minimal disruption to the existing solar concentrator infrastructures.